Performance based planning of complex urban social-ecological systems: The quest for sustainability through the promotion of resilience - Botequilha-Leitão, André (2022)
Urban systems and human settlements have been growing exponentially in size and complexity in the last decades, defying current approaches to sustainable development. While urban planning has been identified as one of the main tools for attaining specific sustainability goals, consideration of cities as complex social-ecological and adaptive systems challenges traditional views, demanding new flexible and creative planning solutions. In this conceptual study, we analyse the capacity of performance-based planning (PBP) to provide sustainable solutions for urban planning problems. To do so, we examine the different conceptualizations of PBP in the current planning environment. To better define the challenges posed by the complexity of urban systems, we explore the similarities and common ground between PBP and other approaches such as adaptive planning and management (APM) and problem structuring methods (PSM). We analyse a case study, in Queensland (Australia), using SWOT (Strengths, Weaknesses, Opportunities and Threats) analysis to identify potential advantages and barriers to the implementation of PBP. Finally, we discuss the potential role of APM and PSM in PBP, the utility of an extended conceptualization of resilience as an important reference for its implementation and a potentially stronger role for planners in PBP as decision shapers.